Post-Pandemic Human Resource Management Strategy Through Work From Anywhere (WFA), Monitoring Employee Productivity and Skill Development - Nugraha, Irpan Bangga; Soegoto, Dedi Sulistiyo (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The emergence of the COVID-19 pandemic has dramatically changed the way we live and work. This has reset work trends resulting in HR leaders being forced to rethink employee and workforce planning. In addition, employees must learn how to change to new work systems such as online communication with clients and colleagues, teleworking, and facing technological challenges. The purpose of this study is to find out what strategies are carried out by leaders after the pandemic. This type of research is qualitative research by conducting observations, interviews, and literacy studies. The study’s result are leaders dealing with the post-Covid-19 pandemic period can do 3 things, namely working from anywhere (WFA), monitoring employee productivity, and skill development.